Renal outcome in human immunodeficiency virus (HIV) infected patients on highly active antiretroviral therapy (HAART) - Sinyiza, Frank Watson (My University, 2016)
BACKGROUND: Renal dysfunction is an increasingly recognized co-morbidity among HIV-infected patients on HAART. Progression to end stage renal disease impacts negatively on morbidity and mortality. I evaluated factors for the development and progression of renal disease, and estimated the incidence and prevalence of CKD stage 3 or worse at an HIV clinic in Johannesburg. METHODS: A retrospective study was conducted involving two cohorts of HIV-infected adults on HAART attending Themba Lethu Clinic in Johannesburg, South Africa, from June 2010 to May 2012. The first cohort, the incident cohort, involved patients initiated on HAART between June 2010 and May 2012 with normal baseline renal function. The primary outcome from this study cohort was doubling of serum creatinine from baseline or development of end stage renal disease. The second cohort (prevalent cohort) analysis included HIV-infected patients on HAART during the period under study. Patient data was extracted from Therapy Edge, an electronic database. RESULTS: From the incident cohort, 2424 patients met entry criteria, of whom 93 (3.8%) developed renal dysfunction after initiation of HAART, with an incidence of acute renal disease and chronic kidney disease of 2.9% and 0.9% respectively. A total of 28 (1.2%) patients developed either end stage renal disease requiring dialysis or doubled serum creatinine from the baseline. The mean duration for development of end stage renal disease or doubling of serum creatinine was 10.21 months (range of two weeks to 38 months). From the prevalent cohort, 2500 HIV-infected adults met the inclusion criteria, of whom 58 had CKD, with a prevalence of 2.3% (95% CI 0.02- 0.03). Male sex, hypertension, low body mass index, low CD4 count and TDF based regimen were predictors of decline in renal function. CONCLUSION: Doubling of serum creatinine or development of end stage renal disease after initiation of HAART was an uncommon finding and the overall incidence and prevalence of chronic kidney disease was low. Screening for evidence of renal dysfunction in HIV-infected patients and treatment of traditional risk factors for CKD are still important for preventing further renal damage.
A research report submitted in partial fulfillment of the requirements for the degree of Masters of Medicine in Internal Medicine, Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, South Africa. Johannesburg, 2015